Autobiography and Self-Reflection in Alexander Solzhenitsyn’s “The GULAG Archipelago” - Nellya M. Shсhedrina (Izvestiâ Ûžnogo Federalʹnogo Universiteta: Filologičeskie Nauki, 2021)
“The GULAG Archipelago” is based on historical and autobiographical material. Autobiography is a key feature of the works of Alexander Solzhenitsyn. This style trait manifests itself in the plot, composition, is expressed in the ways of self-reflection, methods of self-identification, in the functions and role of the author-narrator. The retrospective component, as well as the identity of the author and the narrator, the identity of the author and the character, are of fundamental importance. The type of narration chosen by Solzhenitsyn for “The Archipelago” opened up inexhaustible possibilities of fictional and documentary prose as a genre that conceals a way of correlating autobiographical and factual material. At the same time, the author was also a witness to what was happening and conveyed the details, the spirit of his time. Solzhenitsyn’s autobiography is special: it is not only the use of the facts of the writer’s biography, it is the desire to convey their thoughts as a result of the experience through the psychological experiences, thoughts and feelings of the author. The writer draws a spiritual rebirth of a person in the labor camp, reveals moments of repentance, the development of spiritual stoicism. Hard labor elevated Solzhenitsyn and became the highest point from which the most important stages of his life can be counted.